Literature Review Aborsi Akibat Pemerkosaan Dalam Perspektif Hukum Islam - Khairunnisa, Khairunnisa (UNES Law Review, 2024)
In principle, abortion is prohibited in all forms of law, whether it be positive law or Islamic law, as it is considered premeditated murder of the life of an unborn individual. However, there are certain situations that provide exceptions to perform abortion, such as in cases of rape or when there is a serious threat to the life of the mother. In this context, there is an ongoing debate regarding these exceptions, making it important to conduct thorough research on this issue.